1996
DOI: 10.1172/jci118709
|View full text |Cite
|
Sign up to set email alerts
|

Obesity/insulin resistance is associated with endothelial dysfunction. Implications for the syndrome of insulin resistance.

Abstract: To test the hypothesis that obesity/insulin resistance impairs both endothelium-dependent vasodilation and insulinmediated augmentation of endothelium-dependent vasodilation, we studied leg blood flow (LBF) responses to graded intrafemoral artery infusions of methacholine chloride (MCh) or sodium nitroprusside (SNP) during saline infusion and euglycemic hyperinsulinemia in lean insulin-sensitive controls (C), in obese insulin-resistant subjects (OB), and in subjects with non-insulin-dependent diabetes mellitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

69
1,028
14
31

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,540 publications
(1,149 citation statements)
references
References 61 publications
69
1,028
14
31
Order By: Relevance
“…p values are given for comparisons between groups tested with non-parametric, t test and Chi square tests cardiovascular dysfunction occurred in both at arterial and at cardiac myocyte levels as an independent risk factor of obesity. However, all animal and clinical studies examining vascular function in obesity have shown some degree of vascular abnormalities that occur at both endothelial and smooth muscle levels [18][19][20]. The correlation of lipid abnormalities with obesity, diabetes as well as with the MetS may also implicate involvement of BChE.…”
Section: Discussionmentioning
confidence: 99%
“…p values are given for comparisons between groups tested with non-parametric, t test and Chi square tests cardiovascular dysfunction occurred in both at arterial and at cardiac myocyte levels as an independent risk factor of obesity. However, all animal and clinical studies examining vascular function in obesity have shown some degree of vascular abnormalities that occur at both endothelial and smooth muscle levels [18][19][20]. The correlation of lipid abnormalities with obesity, diabetes as well as with the MetS may also implicate involvement of BChE.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Interestingly, endo- thelial dysfunction favours vasoconstriction and BP elevations during glucose and insulin infusions. [10][11][12][13][14]23 Endothelial dysfunction has been observed in hypertensives, obese and type-2 diabetics; conditions characterised by the presence of insulin resistance, compensatory hyperinsulinaemia and glucose intolerance. [12][13][14] Consequently, both hyperinsulinaemia and hyperglycaemia may play a role in the hypertension of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] It is thus possible, that the small increase in glucose and insulin induced by oral glucose in lean normotensives produced a small, but significant BP reduction. In fact, insulin-induces vasodilation in normal subjects [8][9][10][11][12][13][14] and glucose induces minimal BP changes in healthy animals'. 23 The failure to observe BP lowering in obese hypertensives is most likely due to hyperglycaemia and hyperinsulinaemia in the presence of insulin resistance and to possible endothelial dysfunction.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the key role that the vascular endothelium plays in atherogenesis, it is not surprising that major cardiovascular risk factors such as hypercholesterolaemia, 8 type 2 diabetes, 21 hypertension, 22 ageing, male gender and smoking, 23 are all accompanied by vascular endothelial dysfunction.…”
Section: Vascular Endothelial Functionmentioning
confidence: 99%